Biotechnological approaches to develop resistant rice cultivars against bacterial panicle blight disease - Md Hatta, Muhammad Asyraf; Azmi, Asyraf; Mohd Azhan, Mohamad Iqbal Hakim; Zainuddin, Fatin ‘alyaa (Malaysian Society for Biochemistry & Molecular Biology (MSBMB), 2024)
Bacterial Panicle Blight (BPB) caused by Burkholderia glumae is one of the severe seed-borne bacterial diseases of rice that has affected major rice producing countries worldwide. Over 70% of harvested rice exhibited grain rot or empty grain were reported from the infected fields. The development of disease-resistant rice cultivars remains to be the most sustainable approach to control this disease as opposed to chemical applications. However, rice cultivars that exhibit complete resistance to BPB is yet to be developed for deployment. Over the last century, conventional method has been used by breeders and cytogeneticists to introgress resistance (R) genes for crop improvement. The employment of this approach alone is often associated with a lengthy period and the simultaneous introduction of genetically linked undesired traits. The integration of genomics and molecular genetics into the conventional method has facilitated the breeding efforts in recent times. In this review, we discuss how recent advances in biotechnology can help to accelerate the process of developing resistant rice cultivars against bacterial panicle blight disease.